The plant paradox cookbook : 100 delicious recipes to help you lose weight, heal your gut, and live lectin-free - Gundry, Steven R. (Harper Wave, an imprint of HarperCollinsPublishers, 2018)
From renowned cardiac surgeon and acclaimed author Dr. Steven R. Gundry, the companion cookbook to New York Times bestselling THE PLANT PARADOX, offering 100 easy-to-follow recipes and four-color photos. In the New York Times bestseller The Plant Paradox, Dr. Steven Gundry introduced readers to the hidden toxins lurking in seemingly healthy foods like tomatoes, zucchini, quinoa, and brown rice: a class of plant-based proteins called lectins. Many people are familiar with one of the most predominant lectins--a substance called gluten, which is found in wheat and other grains. But while cutting out the bread and going gluten-free is relatively straightforward, going lectin-free is no small task. Now, in The Plant Paradox Cookbook, Dr. Gundry breaks down lectin-free eating step by step and shares one hundred of his favorite healthy recipes. Dr. Gundry will offer an overview of his Plant Paradox program and show readers how to overhaul their pantries and shopping lists to make delicious, simple, seasonal, lectin-free meals. He'll also share his hacks for making high-lectin foods safe to eat, including methods like pressure-cooking grains and peeling and deseeding tomatoes. With a quick-start program designed to boost weight loss and recipes for smoothies, breakfasts, main meals, snacks, and desserts, The Plant Paradox Cookbook will show readers of The Plant Paradox--and more--how delicious it can be to eat lectin-free.